The Relationship Between Providing Supplementary Food to Pregnant Women with Special Needs and the Incidence of Low Birth Weight (LBW) at the Karanggede Community Health Center, Boyolali - Enggrik Oktoria Sari; Triani Yuliastanti; Sri Handayani (JURNAL KEBIDANAN KESTRA (JKK), 2026)
Background. LBW is influenced by the mother’s nutritional status (malnutrition). One strategy to improve the nutrition of malnourished pregnant women is the provision of supplementary food. According to Ministry of Health Regulation No. 51 of 2016 regarding Standards for Nutritional Supplementation Products and the Provision of Supplementary Feeding (PMT) for Pregnant Women, the provision of supplementary feeding for pregnant women has been implemented in Boyolali Regency.The objective of this study is to determine the relationship between the intervention of providing supplementary feeding to pregnant women with KEK and the incidence of LBW at the Karanggede Public Health Center in Boyolali. Methods. This was a quantitative study using an analytical survey design, specifically a case-control study. The study population consisted of all pregnant women with KEK at the Karanggede Community Health Center from January to December 2025, totaling 97 pregnant women. The sample in this study consisted of 30 pregnant women with KEK who received PMT in 2025, plus 30 pregnant women with KEK who did not receive PMT in 2025. In this study, 30 of the 67 pregnant women with KEK who did not receive PMT were selected at random. All pregnant women with KEK who received PMT were included. Data analysis was performed using the chi-square test. Research results. The incidence of LBW at the Karanggede Community Health Center was predominantly non-LBW, with 52 respondents (86.7%). There is an association between the PMT intervention for pregnant women with KEK and the incidence of LBW at the Karanggede Community Health Center in Boyolali (p-value 0.049), with an OR of 8.826, meaning that PMT administration reduces the incidence of LBW by 8.8 times compared to pregnant women with KEK who did not receive PMT. Conclusion. There is an association between the intervention of providing supplementary food to pregnant women with KEK and the incidence of LBW at the Karanggede Boyolali Community Health Center. The research results can be used as input to conduct education on the causes of LBW among mothers before pregnancy and during pregnancy.